Description of the Basic Technical Skills of Junior Football Players' Passing-Control and Shooting - Andriadi Andriadi; Eka Supriatna; Rubiyatno Rubiyatno; Yohanes Touvan Juni Samodra; Putra Sastaman B (Universitas Majalengka, 2023)
The ability to take free kicks is owned by every soccer player, as are passing and control abilities. Mastery of these two techniques is very important for a soccer player. This study aims to describe the ability to do free kicks and control passing. The research method used is a survey and is descriptive research. The sample is 15 football athletes at the Mensemat club in Sambar Regency, West Kalimantan. Athletes are given control-passing tests and free calm tests. The data were analysed with descriptive statistics. The results showed that the ability to do free kicks and control passing was still 6% in the bad category; the rest were good or very good. Meanwhile, there are still 13% of free kick abilities in the bad category, and the rest are good or very good.